A new bio-based fibre-reinforced polymer obtained from sheep wool short fibres and PLA. Issue 2 (5th November 2019) - Aldas Carrasco, Miguel Fernando; Rouault, Nicolas Jérôme; Ferri Azor, José Miguel; López-Martínez, Juan; Samper Madrigal, María Dolores
Abstract : Within the cheese industry is used the milk of a specific species of sheep whose wool is not suitable for the fibre industry. Therefore, this fibre becomes a waste by-product. To take advantage of this waste, the formulation of a fibre-reinforced polymer based on a poly(lactic acid) (PLA) matrix plasticised with maleinised linseed oil (MLO) is proposed. The work began by evaluating the feasibility of four fibre-cleaning processes. Then, to study the composition and processing conditions of the material, a complete factorial design of experiment 2 2, improved with four centre-points, was considered. Afterwards, the mechanical and thermal properties of the formulations were assessed. The results showed that the most suitable washing method was the one similar to the industrial cleaning process. The reprocessing of the material increased its homogeneity due to an improvement in the fibre–matrix interface. The Pareto chart showed that there was no interaction between the wool content and the number of times the material was reprocessed. In general, the addition of sheep wool to a PLA/MLO matrix did not significantly modify the mechanical and thermal properties of the matrix. These results indicate a viable alternative to reduce the wool waste generated in the food industry by means of new bio-based material formulations.